Recent advancement in polymer/halloysite nanotube nanocomposites for biomedical applications - Mohamed Haneef, Intan Najwa Humaira; Shaffiar, Norhashimah; Buys, Yose Fachmi; Syed Shaharuddin, Sharifah Imihezri; Abdul Hamid, Abd. Malek; Widiyati, Khusnun (John Wiley and Sons Inc, 2022)
Halloysite nanotubes (HNTs) have recently been the subject of extensive research as a reinforcing filler. HNT is a natural nanoclay, non-toxic and biocompatible, hence, applicable in biomedical fields. This review focuses on the mechanical, thermal, and functional properties of polymer nanocomposites with HNT as a reinforcing agent from an experimental and theoretical perspective. In addition, this review also highlights the recent applications of polymer/HNT nanocomposites in the biomedical fields